Slow-release self-adaptive expansion microcapsule, preparation method and cement-based material

By combining sustained release adaptive expansion microcapsules with cement-based materials in tunnel construction, the problem of poor sealing effect of cement slurry when facing a large amount of water or mud is solved, and an effective anti-breathing and leakage prevention effect is achieved.

CN119191742AActive Publication Date: 2024-12-27SHANDONG UNIV +3

Patent Information

Application Number
CN202411126303.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2024-12-27
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

In tunnel construction, cement slurry is easily dispersed when facing a large amount of water or mud, resulting in poor sealing effect or failure, and it is impossible to effectively prevent leakage and leakage.

Method used

Use sustained-release adaptive expansion microcapsules to prepare sustained-release adaptive expansion agent by encapsulating high-water absorption materials through microcapsules, and pump them into the target area at the same time as cement-based materials. The microcapsules are used to sustained-release expansion after encountering water to achieve adaptive anti-trajectory Plug the leak.

Benefits of technology

After the cement continues to hydrate and harden, the water and mud leaks are completely sealed, which improves the sealing effect and ensures the adaptive anti-bumping effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191742A_ABST
    Figure CN119191742A_ABST
Patent Text Reader

Abstract

The invention discloses a slow-release self-adaptive expansion microcapsule, a preparation method and a cement-based material, the slow-release self-adaptive expansion microcapsule is of a core-shell structure, and the core-shell structure comprises a plurality of cores composed of 100 parts of an expanding agent, 5-15 parts of an adhesive and 10-25 parts of an active filler; the shell is formed by 5-20 parts of a coating agent; wherein the shell covers the plurality of cores and forms a core-shell structure; the shell can be dissolved in a liquid environment to release the plurality of cores to absorb the liquid and create expansion. The microcapsule has a core-shell double-layer structure, and comprises an outer polymer shell layer and an inner core, wherein the inner core contains a self-adaptive expansion material, and the outer polymer shell layer serves as an outer layer. The external polymer shell layer ensures the slow release effect of the microcapsule, and meanwhile protects the inner core from being influenced by water in cement paste, and the inner core can be pumped to a target layer along with the paste; the internal expansion material core ensures that the capsule can rapidly absorb water and expand after being released, so that the aims of preventing channeling and leaking stoppage are fulfilled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional building materials, and in particular to a slow-release adaptive expansion microcapsule, a preparation method and a cement-based material. Background Art

[0002] When constructing tunnels under different geological conditions, tunnel accidents may sometimes occur, including landslides and water inrush. Once a tunnel is located under a lake, river or other water body and water or mud spitting occurs, cement slurry is often used for anti-channeling and plugging construction. However, when the amount of water or mud is large, the plugging cement slurry will be dispersed. The presence of a large amount of water will prevent the hydration of cement, which will in turn affect the coagulation and hardening of the cement slurry. The leak cannot be plugged, resulting in poor plugging effect, or even complete failure of the plugging operation. Summary of the invention

[0003] In view of this, the present application provides a slow-release adaptive expansion microcapsule, a preparation method and a cement-based material. The microcapsule is used to encapsulate a highly absorbent material to prepare a slow-release adaptive expansion agent, which is pumped into the target area simultaneously with the cement-based material to achieve the effect of adaptive anti-channeling and leakage plugging.

[0004] The embodiment of the present application is implemented as follows: the present application provides a sustained-release adaptive expansion microcapsule, wherein the sustained-release adaptive expansion microcapsule is a core-shell structure, and the core-shell structure has:

[0005] A plurality of cores consisting of 100 parts of a swelling agent, 5 to 15 parts of a binder, and 10 to 25 parts of an active filler; and

[0006] A shell formed from 5 to 20 parts of a coating agent;

[0007] The shell covers the plurality of cores to form the core-shell structure; the shell can be dissolved in a liquid environment to release the plurality of cores to absorb liquid and swell.

[0008] In some embodiments, the mass ratio of the shell to the core is 0.05 to 0.1:1; or

[0009] The thickness of the shell is 0.1-0.5 mm, and the average particle size of the core is 0.5-2.0 mm.

[0010] In some embodiments, each of the shells contains 10 to 20 cores; there is a gap between the core and the shell, so that the porosity of the core-shell structure is greater than 0 and less than or equal to 1%.

[0011] In some embodiments, the liquid environment has any one of acidic, neutral, and alkaline properties;

[0012] Wherein, the dissolution time of the shell in an acidic liquid environment is 2.5 to 10 minutes; or

[0013] The shell dissolves in an alkaline liquid environment for 20 to 120 minutes; or

[0014] The shell dissolves in a neutral liquid environment for 240 to 540 minutes.

[0015] In some embodiments, the expansion agent is selected from at least one of an expandable water-absorbing resin, an expandable silicate cement, and sodium polyacrylate;

[0016] The adhesive is selected from at least one of polyurethane glue, ethyl cellulose, hydroxypropyl methyl cellulose, and sodium silicate; or

[0017] The active filler is selected from at least one of granulated blast furnace slag, metakaolin and fly ash.

[0018] In some embodiments, the coating agent is selected from at least one of ethyl cellulose, microcrystalline cellulose, epoxy resin, and paraffin.

[0019] In some embodiments, the present application also provides a method for preparing sustained-release adaptive expansion microcapsules, comprising the following steps:

[0020] Weigh corresponding parts by weight of a binder and an active filler and dissolve them in a first solvent, and take a clarified portion to obtain a binder solution; mix the binder solution with corresponding parts by weight of an expander, and granulate to obtain spherical particles;

[0021] The coating agent is mixed with the second solvent to obtain a coating solution, and the coating solution is sprayed on the surface of the spherical particles to obtain a sustained-release adaptive expansion microcapsule with a core-shell structure.

[0022] In some embodiments, the first solvent is selected from at least one of methanol, xylene, Tween 80, methyl acetate, and anhydrous ethanol; or

[0023] The second solvent is selected from at least one of methanol, xylene, Tween 80, methyl acetate, and anhydrous ethanol; or

[0024] The spraying adopts a spray drying method, which specifically includes: the spraying time of each 100g of the microcapsules at a flow rate of 0.5mL / s of the coating solution is 10 to 30s, and the drying time is 3 to 10min.

[0025] In some embodiments, the present application also provides a cement-based material, including 100 parts of cement, 100-150 parts of water, 50-100 parts of fine sand, 1-5 parts of water reducer, 0.2-0.8 parts of thickening and water-retaining agent, 0.2-1.5 parts of retarder and 10-20 parts of slow-release adaptive expanding microcapsules.

[0026] In some embodiments, the cement is silicate cement; or

[0027] The fine sand is quartz sand or tailings machine-made sand; or

[0028] The water reducing agent is a polycarboxylate water reducing agent; or

[0029] The thickening and water-retaining agent is selected from at least one of hydroxyethyl cellulose, sodium carboxymethyl cellulose and Wenlun gum; or

[0030] The retarder is selected from at least one of lignin sulfonate, citric acid, tartaric acid and gluconate.

[0031] The beneficial effects of the present application are as follows: the sustained-release adaptive expansion microcapsules of the present application are of a core-shell structure, and the core-shell structure has: multiple cores composed of 100 parts of expansion agent, 5 to 15 parts of adhesive and 10 to 25 parts of active filler; and a shell formed by 5 to 20 parts of coating agent; wherein the shell covers multiple cores and forms a core-shell structure; the shell can be dissolved in a liquid environment to release multiple cores to absorb liquid and swell. The microcapsules of the present application have a core-shell double-layer structure, including an outer polymer shell layer and an inner core containing an adaptive expansion material. The outer polymer shell layer ensures the sustained-release effect of the microcapsules, while protecting the inner core from the water in the cement slurry, and can be pumped to the target layer with the slurry; the inner expansion material core ensures that the capsule can quickly absorb water and swell after release, so as to achieve the purpose of preventing leakage.

[0032] The present application provides a method for preparing a slow-release adaptive expansion microcapsule, characterized in that it comprises the following steps: weighing corresponding mass parts of an adhesive and an active filler and dissolving them in a first solvent, taking a clarified portion to obtain a bonding solution; mixing the bonding solution with corresponding mass parts of an expansion agent, and granulating them to obtain spherical particles; mixing a coating agent with a second solvent to obtain a coating solution, and spraying the coating solution on the surface of the spherical particles to obtain a slow-release adaptive expansion microcapsule with a core-shell structure. The slow-release adaptive expansion agent is prepared by encapsulating a highly absorbent material with microcapsules, and can be pumped into the target area simultaneously with cement concrete. Based on the slow-release effect of the microcapsules in contact with water, the water-absorbing and swollen inner core is released, and a large amount of volume expansion is generated after the inner core absorbs water and achieves physical plugging. The microcapsules prepared by the method of the present application can completely block the sudden water and mud leakage points of the target layer after the cement continues to hydrate and harden, thereby achieving the effect of adaptive anti-channeling and plugging. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the structure of the sustained-release adaptive swelling microcapsule provided in the embodiment of the present application.

[0034] Figure 2 It is a schematic diagram of water absorption and swelling of the sustained-release adaptive swelling microcapsules provided in the examples of the present application. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.

[0036] The present application provides a sustained-release adaptive expansion microcapsule, which is a core-shell structure, and the core-shell structure has: a plurality of cores composed of 100 parts of an expansion agent, 5 to 15 parts of a binder and 10 to 25 parts of an active filler; and a shell formed by 5 to 20 parts of a coating agent;

[0037] The shell covers multiple cores to form a core-shell structure; the shell can be dissolved in a liquid environment to release multiple cores to absorb liquid and swell.

[0038] For further information, see Figure 1 , the gray part in the figure is the shell structure, and the black particles inside are the core structure.

[0039] It is understandable that the core-shell structure can achieve sustained release of active ingredients. Through the dissolution of the shell, the core releases its internal core to absorb liquid. The core part contains a swelling agent. When the microcapsule comes into contact with the liquid, the core absorbs the liquid and expands. This adaptive expansion property can be used to control the size, shape and diffusivity of the microcapsule to adapt it to different application requirements. The role of the shell is to protect the core part from the influence of the external environment, such as humidity, light, oxygen, etc., which helps to enhance the stability of the core and ensure the retention and long-term preservation of the active ingredients. By combining shell layers of different materials, a multi-layer coating structure can be achieved, further improving the stability and sustained release effect of the microcapsule. The interaction between different materials can change the physicochemical properties of the microcapsule, such as controlling the delayed dissolution characteristics of the shell, the adsorption capacity of the core part, etc.

[0040] In some embodiments, the mass ratio of the shell to the core is 0.05 to 0.1: 1. For example, the mass ratio of the shell to the core is any one of 0.05: 1, 0.06: 1, 0.07: 1, 0.08: 1, 0.09: 1, 0.1: 1, or any range between two ratios. By adjusting the ratio of the core to the shell, material selection, and structural design, the responsiveness and release characteristics of the microcapsules under different environments can be regulated.

[0041] In some embodiments, the thickness of the shell is 0.1 to 0.5 mm. For example, the thickness of the shell can be any one of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, and 0.5 mm, or a range between any two values. When the thickness of the shell meets the above range, the shell can be guaranteed to achieve the effect of corrosion inhibition and dissolution in a liquid environment, avoiding premature exposure of the core due to a small shell thickness, or the core cannot be released to absorb the liquid due to a large shell thickness.

[0042] In some embodiments, the average particle size of the core is 0.5 to 2.0 mm. For example, the average particle size of the core can be any one of 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, and 2.0 mm, or a range between any two values. When the average particle size of the core satisfies the above range, the size of the microcapsule can be regulated within a reasonable range, and the core under the average particle size can effectively absorb liquid to produce expansion.

[0043] In some embodiments, 10 to 20 cores are encapsulated in each shell. It is understood that there is a gap between the core and the shell so that the porosity of the core-shell structure is greater than 0 and less than or equal to 1%. The expansion agent particles in the core are bonded into a mass by an adhesive, and the shell layer of the microcapsule will gradually dissolve and become thinner in a liquid environment, and gradually break under the action of water pressure to release the core. When the porosity does not exceed 1%, it can be ensured that enough cores are encapsulated in the microcapsule to improve the expansion effect of the microcapsule.

[0044] In some embodiments, the liquid environment is any one of acidic, neutral, and alkaline. The pH range of the acidic environment is 4 to 5, the pH range of the alkaline environment is 10 to 11, and the pH range of the neutral environment is 7 to 8. The preferred environment range is alkaline conditions, because when the microcapsules are used as plugging materials, the environment of the external cement slurry is alkaline.

[0045] In some embodiments, the dissolution time of the shell in an acidic liquid environment is 2.5 to 10 minutes, such as any one of 2.5 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, and 10 minutes, or a range between any two values.

[0046] In some embodiments, the dissolution time of the shell in an alkaline liquid environment is 20 to 120 min, such as any one of 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, and 120 min, or a range between any two values.

[0047] In some embodiments, the dissolution time of the shell in a neutral liquid environment is 240 to 540 min, such as 240 min, 250 min, 280 min, 300 min, 350 min, 400 min, 450 min, 500 min, 510 min, 520 min, 530 min, 540 min, or any range between any two values.

[0048] In some embodiments, the expansion agent is selected from at least one of an expandable water-absorbing resin, an expandable silicate cement, and sodium polyacrylate. Among them, the expandable water-absorbing resin includes at least one of a low-crosslinked sodium polyacrylate, a starch acrylate polymer, an acrylamide-acrylic acid-sodium p-styrene sulfonate terpolymer, and a starch-acrylonitrile graft copolymer. The water-absorbing and expandable resin is a three-dimensional space network polymer, which is a polymer dielectric. Ionizable ion pairs are embedded in the polymer network chain, and an ion network is formed when it encounters water, and then it absorbs water and expands. The expandable silicate cement uses silicate cement added with calcium sulfoaluminate or lime expansion agents. The calcium sulfoaluminate expansion agent generates calcium sulfonite crystals during the cement hydration process, which produces volume expansion and can be interwoven with fibrous CSH gel microcrystals into a network structure to improve the density and waterproofness of cement stone; the CaO in the lime expansion agent is hydrated into gel-like Ca(OH)2 in the early stage of cement hydration to produce volume expansion, and the gel-like Ca(OH)2 undergoes crystal transformation and becomes larger anisotropic and hexagonal plate-like crystals, which produces volume expansion again. The water absorption principle of sodium polyacrylate is that when sodium polyacrylate comes into contact with water, the carboxyl group (-COOH) in its molecular structure can form hydrogen bonds with water molecules. At the same time, there is an electrostatic repulsion between the molecules of sodium polyacrylate, which causes its molecular chain to unfold and form pores. These pores allow water molecules to penetrate into the interior of sodium polyacrylate, causing it to absorb water and swell. In addition, the molecular structure of sodium polyacrylate also contains a large number of carboxyl groups (-COOH). + ), these carboxyl groups dissociate in water to form negatively charged polyacrylate ions and positively charged sodium ions. Due to the electrostatic repulsion between these ions, the molecular chain of sodium polyacrylate is further extended to form a network structure, thereby increasing its water absorption capacity. In addition, the water absorption of sodium polyacrylate is also affected by its degree of crosslinking. In the case of low crosslinking, water molecules easily penetrate into the polymer, causing the resin to swell, further become hydrophilic and gel, and become a highly water-absorbent state. The crosslinking degree of sodium polyacrylate is related to viscosity. Too low viscosity will cause the material strength to be too low and dissolve in water. Too high viscosity will cause the material swelling degree to decrease, both of which will reduce the material's water absorption capacity. The viscosity range of sodium polyacrylate is 2000-2500mPa.s.

[0049] It is understandable that the above materials can be used as the main materials for the expansion of the inner core, and the above materials can be obtained commercially.

[0050] In some embodiments, the adhesive is selected from at least one of polyurethane glue, ethyl cellulose, hydroxypropyl methylcellulose, and sodium silicate. The adhesive is used to aggregate the expander into a mass to form a granular core. In addition, the adhesive can also absorb a certain amount of liquid in a liquid environment to increase the viscosity and adhesion of the adhesive.

[0051] In some embodiments, the active filler is selected from at least one of granulated blast furnace slag, metakaolin and fly ash. After the inner core absorbs liquid and expands, the active filler can also improve the rheology of cement slurry in the cement slurry environment, improve the early strength of the system, improve the pore structure of cement hardening body, and thus improve durability, and extend the service life of such plugging materials after construction. The active filler plays a filling and lubricating role in the system. The surface of the spherical particles is smooth, which can reduce the internal friction of the system, reduce the water demand, and produce micro-aggregate reaction in an alkaline environment to improve strength.

[0052] In some embodiments, the multiple cores of the present application are composed of 100 parts of expansion agent, 5 to 15 parts of adhesive and 10 to 25 parts of active filler. Among them, when the expansion agent is a resin, it is better matched with the adhesive, has good expansion efficiency and high water absorption multiple and rate, and the cement-based expansion agent is more compatible with the system.

[0053] In some embodiments, the water-swellable resin can further cooperate with the binder to improve the expansion effect. This is because there are microscopic pores or capillaries in the internal structure of the resin. These structures can absorb the binder. After the binder contacts water, it can fill the pores or capillaries. The pressure in the pores or capillaries will decrease, causing water to penetrate into these spaces until the infiltration point, thereby improving the adsorption effect. Adsorption is also an important process for water absorption, similar to the capillary adsorption principle of materials such as cotton, paper, and sponge. The water absorption process of super absorbent resin can be divided into several stages. First, water is absorbed through capillary adsorption and dispersion, and then water molecules act on the hydrophilic groups of the resin through hydrogen bonds, the hydrophilic groups dissociate, and the electrostatic repulsion between ions causes the network of the resin to expand. As the amount of water absorbed increases, the osmotic pressure difference between the inside and outside of the network tends to zero; while the network expands, its elastic contraction force is also increasing, gradually offsetting the electrostatic repulsion of anions, and finally reaching a water absorption balance.

[0054] In some embodiments, the coating agent is selected from at least one of ethyl cellulose, microcrystalline cellulose, epoxy resin, and paraffin. It is understood that the coating agent needs to have the property of being slowly dissolved. Under different environments, by selecting coating agents of different materials to target resistance to different environments, the effect of increasing or decreasing the release time can be achieved.

[0055] In some embodiments, a method for preparing a sustained-release adaptive swelling microcapsule is provided, comprising the following steps:

[0056] Weigh corresponding parts by weight of a binder and an active filler and dissolve them in a first solvent, and take a clarified portion to obtain a binder solution; mix the binder solution with corresponding parts by weight of an expander, and granulate to obtain spherical particles;

[0057] The coating agent is mixed with the second solvent to obtain a coating solution, and the coating solution is sprayed on the surface of the spherical particles to obtain a sustained-release adaptive expansion microcapsule with a core-shell structure.

[0058] Understandably, see Figure 1 The object of coating solution spraying is the core formed by multiple spherical particles.

[0059] In some embodiments, the first solvent is selected from at least one of methanol, xylene, Tween 80, methyl acetate, and anhydrous ethanol.

[0060] In some embodiments, the second solvent is selected from at least one of methanol, xylene, Tween 80, methyl acetate, and anhydrous ethanol.

[0061] In some embodiments, spraying is performed by a spray drying method, specifically comprising: spraying time of 10 to 30 seconds for every 100 g of microcapsules at a flow rate of 0.5 mL / s of the coating solution, and drying time of 3 to 10 minutes. Different granulation schemes can be adopted according to actual needs. For deep repair, multiple spraying methods can be used to increase the thickness of the shell layer to increase the release time of the core.

[0062] In some embodiments, a specific preparation process is provided, wherein the adhesive is mixed with the first solvent in corresponding parts and the active filler, the clarified part of the solution is taken out as the bonding solution, the expansion agent is bonded into a sphere using a disc granulator, the drying is started, and the residual solvent is volatilized using hot air, and then spherical particles are obtained, and the appropriate particle size is screened as the core; then the coating agent and the second solvent are evenly mixed as the coating solution, the disc granulator is used for granulation, the coating agent is sprayed at the turntable to coat the surface of the core particles, and the appropriate particle size is screened as a microcapsule. Depending on the usage scenario, the concentration and coating time of the coating agent can be adjusted, or the core can be coated multiple times, and the thickness and strength of the shell layer can be adjusted to meet the usage requirements of different scenarios.

[0063] In some embodiments, a cement-based material is also provided, comprising 100 parts of cement, 100-150 parts of water, 50-100 parts of fine sand, 1-5 parts of water reducer, 0.2-0.8 parts of thickener and water-retaining agent, 0.2-1.5 parts of retarder and 10-20 parts of slow-release adaptive expansion microcapsules; wherein the slow-release adaptive expansion microcapsules adopt the slow-release adaptive expansion microcapsules of this embodiment; or, the slow-release adaptive expansion microcapsules are the slow-release adaptive expansion microcapsules prepared by the method of this embodiment.

[0064] In some embodiments, the cement is silicate cement, national standard P.O42.5 or 52.5.

[0065] In some embodiments, the fine sand is quartz sand or tailings machine-made sand, which passes through a 1.18 mm square hole sieve, and the fineness modulus is controlled between 1.21 and 1.36.

[0066] In some embodiments, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate of the water reducing agent is between 25% and 35%.

[0067] In some embodiments, the thickening and water-retaining agent is selected from at least one of hydroxyethyl cellulose, sodium carboxymethyl cellulose, and Wenlun gum.

[0068] In some embodiments, the retarder is selected from at least one of lignin sulfonate, citric acid, tartaric acid, and gluconate.

[0069] It can be understood that silicate cement provides an alkaline environment for the system, hardens after microcapsule sealing, and provides strength. The addition of fine sand can control cracks in the system after hardening, reduce the brittleness of the hardened body, and increase strength. Polycarboxylic acid water reducer can greatly reduce the water demand of the system and increase early strength. The thickening and water retention agent can independently adjust the system consistency and water loss. The retarder can control the system setting time according to actual conditions to achieve the purpose of long-distance transportation.

[0070] Before construction, the addition of microcapsules will not significantly change the rheology and water demand of the cement slurry. It can be transported by remote construction methods such as pumping. After arriving at the working location, the microcapsules gradually break and absorb a large amount of nearby aqueous solution to provide sufficient moisture for the condensation of the cement slurry. The released microcapsules are in a colloidal state and will not significantly reduce the alkalinity of the system, ensuring that the strength of the system will not decrease significantly.

[0071] Examples 1-6

[0072] Examples 1-6 provide sustained-release adaptive swellable microcapsules of different components. See Table 1 for specific quantities.

[0073] The method for preparing the sustained-release adaptive expansion microcapsules in Examples 1-6 is the same, specifically: weigh the corresponding mass parts of the adhesive and the active filler and dissolve them in anhydrous ethanol, take the clarified part to obtain the binding solution; mix the binding solution with the corresponding mass parts of the expansion agent and granulate to obtain spherical particles; mix the coating agent with anhydrous ethanol to obtain a coating solution, spray the coating solution on the surface of the spherical particles to obtain a sustained-release adaptive expansion microcapsule with a core-shell structure. Spraying adopts a spray drying method, specifically including: the spraying time of each 100g microcapsule at a flow rate of 0.5mL / s of the coating solution is 20s, and the drying time is 5min.

[0074] Table 1

[0075]

[0076]

[0077] Example 7

[0078] 100 parts of 42.5 silicate cement, 60 parts of quartz sand with a modulus of 1.25, 2 parts of polycarboxylate water reducer, 0.4 parts of hydroxyethyl cellulose, 0.5 parts of lignin sulfonate, 150 parts of water, and 15 parts of the slow-release adaptive expansion microcapsules of Example 1 were selected and mixed to obtain a cement-based material.

[0079] In this embodiment, the setting time of cement is 3.5 hours, and the sustained release time of adaptive expansion microcapsules is 3 hours. Figure 2 The water absorption rate of the expansion agent is 300-500 times of its own weight and the expansion rate is 350-450 times of its volume in a dry state. The rheology of the cement slurry is 25cm and the 24h strength is 14Mpa.

[0080] Example 8

[0081] 100 parts of 42.5 silicate cement, 65 parts of quartz sand with a modulus of 1.30, 1 part of polycarboxylate water reducer, 0.3 parts of sodium hydroxymethyl cellulose, 0.5 parts of citric acid, 120 parts of water, and 10 parts of the slow-release adaptive expansion microcapsules of Example 2 were selected and mixed to obtain a cement-based material.

[0082] In this embodiment, the setting time of cement is 3.5 hours, the slow release time of the adaptive expansion agent is 4 hours, the water absorption rate of the expansion agent measured by the beaker method is 250 to 400 times of its own weight, and the expansion rate is 300 to 400 times of its volume in a dry state. The rheology of the cement slurry is 23 cm, and the 24h strength is 13 Mpa.

[0083] Example 9

[0084] 100 parts of 52.5 silicate cement, 80 parts of quartz sand with a modulus of 1.25, 5 parts of polycarboxylic acid water reducer, 0.4 parts of Wenlun glue, 1.5 parts of tartaric acid, 100 parts of water, and 20 parts of the slow-release adaptive expansion microcapsules of Example 3 were selected and mixed to obtain a cement-based material.

[0085] In this embodiment, the setting time of cement is 3.5h, the slow release time of the adaptive expansion agent is 3.5h, the water absorption rate of the expansion agent measured by the beaker method is 200-300 times of its own weight, and the expansion rate is 150-200 times of its volume in a dry state. The rheology of the cement slurry is 23cm, and the 24h strength is 18Mpa.

[0086] Comparative Example 1

[0087] A cement-based material is provided, the specific composition of which is the same as that of Example 7, except that the slow-release adaptive expansion microcapsules are not added.

[0088] In this comparative example, the setting time of cement is 3.6h, the rheology of cement slurry is 27cm, the 24h strength is 12Mpa, and the water absorption and expansion rate of the system are extremely low. Without the addition of microcapsules, the system cannot absorb water and expand, and when used in anti-leakage work, the reliability will be significantly reduced, and even the strength will not be generated.

[0089] Comparative Example 2

[0090] A cement-based material is provided, the specific composition of which is the same as that of Example 8, except that no water reducing agent is added.

[0091] In this comparative example, the cement setting time is 3h, the slow release time of the adaptive expansion agent is 4h, and the water absorption rate of the expansion agent measured by the beaker method is 250-400 times of its own weight, and the expansion rate is 300-400 times of its volume in a dry state. The rheology of cement slurry is 15cm, and the 24h strength is 11.5Mpa. The water reducer will prolong the setting time of the system. Not adding it will cause the rheological properties of the cement slurry to decrease, the water demand to increase, and the increase in water will cause the strength to decrease. If the water amount is not increased, it will cause pumping difficulties and even block the pump pipe. The reason is that the polycarboxylate water reducer forms an adsorption layer on the surface of cement particles, effectively preventing the mutual adsorption and coagulation between particles, reducing the friction between cement particles, thereby reducing the cohesiveness of the concrete, reducing the water content under the same cement dosage, and achieving the effect of water reduction. This can improve the strength and durability of concrete.

[0092] Comparative Example 3

[0093] A cement-based material is provided, and its specific composition is the same as that of Example 9, except that the inner core material of the microcapsule is a composite of a multi-polymer resin and sodium polyacrylate.

[0094] In this comparative example, the setting time of cement is 3.5h, the slow release time of the adaptive expansion agent is 2.5h, the water absorption rate of the expansion agent measured by the beaker method is 180-260 times of its own weight, and the expansion rate is 130-180 times of its volume in a dry state. The rheology of the cement slurry is 22cm, and the 24h strength is 17Mpa.

[0095] The co-addition of multi-polymer resin and sodium polyacrylate will not significantly improve the water absorption rate, expansion rate and working performance of the system. The control of sustained release time is more difficult. It is difficult to achieve a good coating rate for both cores using the same coating process, which reduces the core release efficiency and increases the workload and cost.

[0096] In summary, the microcapsules of the present application have a core-shell double-layer structure, including an outer polymer shell layer and an inner core containing an adaptive expansion material. The outer polymer shell layer ensures the slow release of the microcapsules, while protecting the core from the water in the cement slurry, and can be pumped to the target layer with the slurry; the inner expansion material core ensures that the capsule can quickly absorb water and expand after release, which can achieve the purpose of preventing leakage.

[0097] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0098] The products and preparation methods provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A sustained-release adaptive expansion microcapsule, characterized in that: The sustained-release adaptive expansion microcapsule is a core-shell structure, and the core-shell structure has: A plurality of cores consisting of 100 parts of a swelling agent, 5 to 15 parts of a binder and 10 to 25 parts of an active filler; as well as A shell formed from 5 to 20 parts of a coating agent; The shell covers the plurality of cores to form the core-shell structure; the shell can be dissolved in a liquid environment to release the plurality of cores to absorb liquid and swell.

2. The sustained-release adaptive swelling microcapsule according to claim 1, characterized in that: The mass ratio of the shell to the core is 0.05 to 0.1:1; or The thickness of the shell is 0.1-0.5 mm, and the average particle size of the core is 0.5-2.0 mm.

3. The sustained-release adaptive swelling microcapsule according to claim 1, characterized in that: Each of the shells contains 10 to 20 cores; there is a gap between the core and the shell, so that the porosity of the core-shell structure is greater than 0 and less than or equal to 1%.

4. The sustained-release adaptive swelling microcapsule according to claim 1, characterized in that: The liquid environment is any one of acidic, neutral and alkaline; Wherein, the dissolution time of the shell in an acidic liquid environment is 2.5 to 10 minutes; or The shell dissolves in an alkaline liquid environment for 20 to 120 minutes; or The shell dissolves in a neutral liquid environment for 240 to 540 minutes.

5. The sustained-release adaptive swelling microcapsule according to claim 1, characterized in that: The expansion agent is selected from at least one of an expandable water-absorbing resin, an expandable silicate cement, and sodium polyacrylate; The adhesive is selected from at least one of polyurethane glue, ethyl cellulose, hydroxypropyl methyl cellulose, and sodium silicate; or The active filler is selected from at least one of granulated blast furnace slag, metakaolin and fly ash.

6. The sustained-release adaptive swelling microcapsule according to claim 1, characterized in that: The coating agent is selected from at least one of ethyl cellulose, microcrystalline cellulose, epoxy resin and paraffin.

7. A method for preparing the sustained-release adaptive swellable microcapsules according to any one of claims 1 to 6, characterized in that: The following steps are involved: Weigh corresponding parts by weight of a binder and an active filler and dissolve them in a first solvent, and take a clarified portion to obtain a binder solution; mix the binder solution with corresponding parts by weight of an expander, and granulate to obtain spherical particles; The coating agent is mixed with the second solvent to obtain a coating solution, and the coating solution is sprayed on the surface of the spherical particles to obtain a sustained-release adaptive expansion microcapsule with a core-shell structure.

8. The method for preparing sustained-release adaptive swelling microcapsules according to claim 7, characterized in that: The first solvent is selected from at least one of methanol, xylene, Tween 80, methyl acetate, and anhydrous ethanol; or The second solvent is selected from at least one of methanol, xylene, Tween 80, methyl acetate, and anhydrous ethanol; or The spraying adopts a spray drying method, which specifically includes: the spraying time of each 100g of the microcapsules at a flow rate of 0.5mL / s of the coating solution is 10 to 30s, and the drying time is 3 to 10min.

9. A cement-based material comprising 100 parts of cement, 100-150 parts of water, 50-100 parts of fine sand, 1-5 parts of a water reducing agent, 0.2-0.8 parts of a thickening and water retaining agent, 0.2-1.5 parts of a retarder, and 10-20 parts of slow-release adaptive expansion microcapsules; in, The sustained-release adaptive swelling microcapsule is the sustained-release adaptive swelling microcapsule described in any one of claims 1-6; or, the sustained-release adaptive swelling microcapsule is the sustained-release adaptive swelling microcapsule prepared by the method described in any one of claims 7-8.

10. A cement-based material according to claim 9, characterized in that: The cement is silicate cement; or The fine sand is quartz sand or tailings machine-made sand; or The water reducing agent is a polycarboxylate water reducing agent; or The thickening and water-retaining agent is selected from at least one of hydroxyethyl cellulose, sodium carboxymethyl cellulose and Wenlun gum; or The retarder is selected from at least one of lignin sulfonate, citric acid, tartaric acid and gluconate.

Citation Information

Patent Citations

  • High-performance concrete with ultrahigh strength and preparation method thereof

    CN107963855A

  • Environmental complex response homogeneous expansion type self-repairing microcapsule for concrete and preparation method thereof

    CN114933441A

  • High-strength water-absorbent resin microcapsule as well as preparation method and application thereof

    CN115260535A

  • Slow-release controllable grouting and water plugging material as well as preparation method and application thereof

    CN115651421A

  • Lightweight cement product and method for producing the product

    JP2004131361A

Cited By

  • Rare earth-containing modified sulphoaluminate cement protective material and preparation method thereof

    CN119490341A

  • High-temperature-resistant grouting and water plugging material for underground engineering and preparation method thereof

    CN119874319A

  • Oil-soluble temporary plugging agent with multiple layers of microcapsules and preparation method of oil-soluble temporary plugging agent

    CN120865870A

  • Water-control type fixed-point solidification composite material for deep mudstone reinforcement and preparation method and application of water-control type fixed-point solidification composite material

    CN121021054A

  • Copper tailing-based high-strength grouting material and preparation method thereof

    CN122233745A